Whole-genome sequencing-based prediction and analysis of antimicrobial resistance in Yersinia enterocolitica from Ningxia, China - Yue, Yuan; Shen, Mei; Liu, Xiang; Hao, Qiong; Kang, Yutong; Che, Yanlin; Li, Fang; Chen, Shenglin; Xu, Shuai; Jing, Huaiqi; Li, Zhen-jun; Zhou, Xue-zhang (Frontiers in Microbiology, 2022)
Focusing on resistance trends and transmission patterns of pathogenic microorganisms is a major priority for national surveillance programmes. The use of whole-genome sequencing for antimicrobial susceptibility testing (WGS-AST) is a powerful alternative to traditional microbiology laboratory methods. Yersinia enterocolitica antimicrobial resistance (AMR) in the Ningxia Hui Autonomous Region has yet to be described thoroughly in current studies. We assessed and monitored the development of Y. enterocolitica AMR in the Ningxia Hui Autonomous Region during 2007 to 2019 based on WGS-AST. Resistance genotypes were predicted based on WGS. Antimicrobial resistance testing using classical microbiology determined resistance to 13 antimicrobial agents in 189 Y. enterocolitica isolates from Ningxia. The highest resistance level was 97.88% for cefazolin, followed by ampicillin (AMP) (44.97%), ciprofloxacin (CIP) (25.40%), streptomycin (STR) (11.11%), and tetracycline (TET) (10.58%). Isolates emerged as chloramphenicol (CHL) and trimethoprim/sulfamethoxazole (SXT) resistant. The primary plasmid types were IncFII(Y) and ColRNAI. The TET, STR, and SXT resistance were mediated by the tetA, aph(6)-Id, aph(3'')-Ib, and sul2 genes located on the IncQ1 plasmid. The resistant strains were predominantly biotype 4/O:3/ST429 and the hosts were pigs and patients. The number of multidrug-resistant (MDR) strains was of concern, at 27.51%. At present, the prediction of antimicrobial resistance based on WGS requires a combination of phenotypes. From 2007 to 2019, Y. enterocolitica isolates from the Ningxia Hui Autonomous Region showed a relatively high rate of resistance to cefazolin (CZO) and some resistance to AMP, CIP, STR, and TET. CIP, SXT, and TET showed a relatively clear trend of increasing resistance. Plasmids carrying multiple drug resistance genes are an important mechanism for the spread of antimicrobial resistance. Isolates with low pathogenicity were more likely to present an AMR phenotype than non-pathogenic isolates.